The Impact of Family Wealth on Asset Return: A Moderated Chain Median Model Partially Explaining Wealth Inequality - Tianye Tu (Behavioral Sciences)
Global wealth is distributed highly unequally, and this issue has worsened in recent years. Such inequality threatens human well-being and fundamental values. In response, this paper aims to explore the wealth inequality phenomenon from the perspective of investment psychology. Recognizing wealth return heterogeneity as a crucial source of inequality, the paper establishes a psychological model focused on two investment skill factors that can partially explain this heterogeneity. The theoretical foundation of this model includes the conservation of resources (COR) theory, prospect theory, and performance determinants theory. In our model, risk preference and asset-holding periods sequentially mediate the relationship between family wealth and asset returns. Moreover, risk preference and the disposition effect are identified as serial mediators in this relationship. Financial literacy also moderates the relationship between the risk preference, asset-holding period, and disposition effect. This proposed model not only provides a richer explanation for wealth return heterogeneity through the lens of investment skill but also extends the application of COR theory to investment psychology, thereby enhancing our understanding of resources. Moreover, it offers a novel explanation for the relationship between risk preference and the deposition effect, enriching prospect theory. Finally, the inclusion of financial literacy’s role broadens the scope of performance determinants theory.